A training program based on the SWOM model, in developing creative teaching skills with students of the Islamic Studies Curriculum Department at the College of Education, Sana’a - Al-Yusufi, AbdulRahman Qaid Abdullah; Al-Mekhlafi, AbdulSalam Abdo Qasim (Journal of Curriculum and Teaching Methodology, 2024)
The research aimed to determine the effectiveness of a training program based on the school wide optimum model (SWOM): in developing creative teaching skills among student teachers in the Department of Islamic Studies Curricula at the College of Education, Sana’a. The researchers used the descriptive approach, the construction and development method, in preparing a list. Creative teaching skills, in building the training program, the trainee’s guide, and the quasi-experimental approach in designing the experiment, “one-group-based design,” with pre- and post-measurement, which was applied to a random sample of (20) male and female students, The tool consisted of a note card consisting of (46) skills, and the results revealed that there were statistically significant differences at the (0.000) level between the averages of the experimental group in the pre- and post-application of the note card, where in the pre-test it obtained an average of (112.80 Who 230) versus (214.55) for the post-test, in favor of the post-application. It was also shown that the training program based on the SWOM model has great effectiveness in developing the creative teaching skills of the group members with a rate of gain adjusted for the size of the effectiveness (1.31), which is a value greater than the ratio (1.2) specified for great effectiveness. Based on the results, the researchers recommended the need to circulate the training program to other samples, train them through it, and develop programs to prepare Islamic education teachers to include modern teaching strategies, most notably the SOM model, in addition to proposals for complementary studies on the subject.
Keywords: SWOM model; creative teaching; training program